2015
DOI: 10.1039/c4ee03707c
|View full text |Cite
|
Sign up to set email alerts
|

Unique 3D heterojunction photoanode design to harness charge transfer for efficient and stable photoelectrochemical water splitting

Abstract: The hierarchically CoOxdecorated 2D C3N4nanosheet–1D/2D nanorod/nanosheet-assembled barium-doped TaON array as 3D heterojunction photoanode exhibited the enhanced photocurrent density and durable photostability for photoelectrochemical solar water splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 52 publications
2
56
0
Order By: Relevance
“…Accordingly, as‐established Bi 4 V 2 O 11 /CeO 2 forms a type I band alignment (Figure h) . This configuration can facilitate the interfacial electrons transfer from CeO 2 to Bi 4 V 2 O 11 as illustrated in Figure i, which can be verified by the drastic decrease of photoluminescence (PL) intensity (Supporting Information, Figure S14) . Remarkably, because amorphous structure can induce band bending for promoted charge transfer at interfaces, BVC‐A displays a much lower PL intensity (Figure g) and a smaller diameter of semicircular Nyquist plots (Supporting Information, Figure S15) relative to BVC‐C …”
Section: Methodsmentioning
confidence: 76%
“…Accordingly, as‐established Bi 4 V 2 O 11 /CeO 2 forms a type I band alignment (Figure h) . This configuration can facilitate the interfacial electrons transfer from CeO 2 to Bi 4 V 2 O 11 as illustrated in Figure i, which can be verified by the drastic decrease of photoluminescence (PL) intensity (Supporting Information, Figure S14) . Remarkably, because amorphous structure can induce band bending for promoted charge transfer at interfaces, BVC‐A displays a much lower PL intensity (Figure g) and a smaller diameter of semicircular Nyquist plots (Supporting Information, Figure S15) relative to BVC‐C …”
Section: Methodsmentioning
confidence: 76%
“…in less than 10 min (@ 1.2V vs. RHE). Recently, Hou et al 165 reported a non-metallic graphitic C 3 N 4 coated 3D structured n-TaON with CoO X co-catalyst that shows significantly enhanced photoelectrochemical stability (3 hours) under OER condition at pH 13.6 (1M NaOH). In addition, negative band offsets for both CB and VB (-1.0 eV and -0.5 eV, respectively) toward the TaON promote an effective charge separation for water oxidation reaction.…”
Section: Other Layersmentioning
confidence: 99%
“…Calculated from UV/Vis DRS (Supporting Information, Figure S13), the band gap values are 2.15 and 3.05 eV for Bi 4 V 2 O 11 and CeO 2 ,r espectively,a s shown in the corresponding Kubelka-Munk plot (Figure 2f). [45] Remarkably,because amorphous structure can induce band bending for promoted charge transfer at interfaces,B VC-A displays am uch lower PL intensity (Figure 2g)a nd as maller diameter of semicircular Nyquist plots (Supporting Information, Figure S15) relative to BVC-C. [46] Another key advantageous feature of designed BVC-A is the integration of amorphous Bi 4 V 2 O 11 with band alignment that may deliver abundant active sites and facilitated electron transport for effective N 2 fixation. [44] This configuration can facilitate the interfacial electrons transfer from CeO 2 to Bi 4 V 2 O 11 as illustrated in Figure 2i,which can be verified by the drastic decrease of photoluminescence (PL) intensity (Supporting Information, Figure S14).…”
Section: Angewandte Chemiementioning
confidence: 99%